Insight into the Structural Disorder in Honeycomb-Ordered Sodium-Layered Oxide Cathodes - Xiao, Lei; Ding, Zhengping; Chen, Cheng; Han, Zhen; Wang, Peng; Huang, Qun; Gao, Peng; Wei, Weifeng (iScience, 2020)
Honeycomb-layered phases Na3M2XO6 (M = Ni, Cu, Co; X = Sb, Bietc.) have been intensively pursued as high-voltage and high-rate capability cathode materials for Na-ion batteries (NIBs), but the crystal structure is not well elucidated. Herein, structural analysis was conducted on pristine Na3Ni2SbO6 material using electron microscopy and associated spectroscopies to reveal its crystallographic features. Experimental observations along multiple zone axes indicate that structural disorder is intrinsic in the pristine Na3Ni2SbO6, characteristic of randomly stacked layers with three variants of monoclinic structure. Stacking disorder is demonstrated by the non-vertical relationship of adjacent Ni2SbO6 layers in [100] zone axis, the different Ni/Sb atomic arrangements in [010] zone axis, and the Ni/Sb random overlap in [001] zone axis. The insight on the structural disorder may inspire studies on their phase transformations upon cycling and provide some clues to potentially solve the voltage/capacity decay problems of these honeycomb-layered materials. [Display omitted] •The intrinsic structural disorder in Na3Ni2SbO6 is unambiguously revealed•Detailed atomic-resolution STEM imaging and crystallography analysis are conducted•The structural disorder is associated with three variants of a monoclinic phase Imaging Methods in Chemistry; Materials Science; Energy Materials